2021
DOI: 10.3390/microorganisms9081773
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug Resistance Bacterial Infections in Critically Ill Patients Admitted with COVID-19

Abstract: Introduction. It is known that bacterial infections represent a common complication during viral respiratory tract infections such as influenza, with a concomitant increase in morbidity and mortality. Nevertheless, the prevalence of bacterial co-infections and secondary infections in critically ill patients affected by coronavirus disease 2019 (COVID-19) is not well understood yet. We performed a review of the literature currently available to examine the incidence of bacterial secondary infections acquired du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 56 publications
2
50
1
7
Order By: Relevance
“…The percentage of patients with Acinetobacter baumanii superinfections in our cohort was significantly higher compared to the results of a review by Pasero et al [ 16 ], where it varied between 0.8–61%, with most studies reporting results between 30 and 40%. The most probable reason for the reported prevalence of Acinetobacter baumanii is the fact that compared to other centers where ICU beds were located in ICUs, in UH Dubrava there was an increased number of ICU beds (85 beds in total, of which around one third were located in rooms that were repurposed to become makeshift ICUs) and reduced nurse/patient ratio, which would need to be 1:1 in mechanically ventilated patients but was 1:2.5–1:3 [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The percentage of patients with Acinetobacter baumanii superinfections in our cohort was significantly higher compared to the results of a review by Pasero et al [ 16 ], where it varied between 0.8–61%, with most studies reporting results between 30 and 40%. The most probable reason for the reported prevalence of Acinetobacter baumanii is the fact that compared to other centers where ICU beds were located in ICUs, in UH Dubrava there was an increased number of ICU beds (85 beds in total, of which around one third were located in rooms that were repurposed to become makeshift ICUs) and reduced nurse/patient ratio, which would need to be 1:1 in mechanically ventilated patients but was 1:2.5–1:3 [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Airway dysfunction, cytopathology and tissue destruction induced by SARS-CoV-2 infection or during bacterial co-infection may facilitate systemic dissemination of the virus and/or bacterial co-pathogens, dramatically increasing the risk of blood infections and sepsis [ 12 , 13 ]. In addition, due to the widely accepted therapeutic regimen of corticosteroid therapy, which reduces COVID-19 mortality [ 14 ] but may promote immunosuppressive states, [ 15 , 16 ] combined with irrational use of antibiotics (in hospital but unfortunately also before hospital admission) [ 17 ], certain ICU stay (non-COVID-19) factors should be also taken into account as contributing factors leading to increased incidence of superinfections: presence of intravascular [ 18 ] and urinary [ 19 ] catheters. Multidrug-resistant pathogen infections are of special concern in these patients due to their deleterious effect on ICU and hospital stays and mortality [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differently, no significant changes were found in carbapenemase-producing Enterobacteriaceae colonization and infection during the two study periods. Concerning the topic of multi-drug resistant (MDR) bacteria secondary infection, Pasero and collaborators performed a review of the literature to investigate the incidence of this important co-infections/superinfections [ 72 ]. According to the authors, most of the studies (mainly retrospective and single-centred) reported low rates of co-infections but a significant incidence of hospital-acquired infections developing about 10–15 days after ICU admission.…”
Section: Main Textmentioning
confidence: 99%
“…LL-37 also kills Candida albicans , most effectively as a cleavage fragment RK-31 ( 30 ). Covid patients in the ICU for more than a few days commonly suffer from co-infections, and often with resistant species of bacteria and fungi, worsening prognosis ( 31 33 ).…”
Section: Introductionmentioning
confidence: 99%